Literatur Review : Toksikologi Industri Dan Keselamatan Kesehatan Kerja Dalam Pengendalian Paparan Bahan Kimia Pada Sektor Manufaktur Dan Rumah Sakit: Indonesia - Sitorus, Mardiah; Sitorus, Rezki Alya Mawaddah; Tampubolon, Selamat Ariady; Hasibuan, Abdurrozzaq (Jurnal Sains Farmasi Dan Kesehatan, 2026)
Industrial toxicology is a branch of science that plays a crucial role in identifying, analyzing, and controlling the impact of chemical exposure on worker health, particularly in the manufacturing and hospital sectors, which have high risk levels. Exposure to chemicals such as organic solvents, heavy metals, disinfectants, and cytotoxic drugs can cause both acute and chronic health problems if not managed properly. This study aims to examine the role of industrial toxicology in controlling chemical exposure and the application of Occupational Safety and Health (OHS) principles to minimize worker health risks. The method used is a literature review by analyzing various national and international journals from the last five years that are relevant to the research topic. The results of the study indicate that effective control of chemical exposure must refer to the hierarchy of control, including elimination, substitution, engineering, administrative control, and the use of personal protective equipment (PPE). In addition, the implementation of a structured OHS management system, continuous worker training, and routine monitoring of the work environment have been proven to reduce exposure levels and the risk of occupational diseases. These findings confirm that the integration of industrial toxicology with a comprehensive OHS system is not merely a formality, but a fundamental necessity for creating a safe, healthy, and productive work environment. Without disciplined controls, long-term risks to workers will continue to be overlooked, leading to a decline in the quality of human resources.